PENGGUNAAN METODE PECS (Picture Exchange Communication System) UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI ANAK AUTIS - Heryati, Euis; Ratnengsih, Een (PEDAGOGIA, 2017)
This study was conducted to test the method of Pecs (Picture Exchange Communication System) as an approach that can be used as an alternative in the communication train children with autism because this method adjusts the communication characteristics and uniqueness of children with autism. This research aims to develop an approach to improve communication skills, knowing the communication skills of children with autism before and after the intervention and determine the extent of the influence of Pecs method to improve the communication skills of children with autism. Subjects in this study were two children with autism who have problems in communication. The method used is an experimental method using Single Subject Research approach to research design A-B-A. These results indicate that the mean level of capability to the subject 1 in the communication capabilities at baseline-A (A-1) of 4.7 in the intervention phase obtaining the mean level of 6.5. While the baseline phase-2 (A-2) after being granted intervention to get the mean level of 10. while the initial ability of the subject 2 in communication skills at baseline-A (A-1) of 5.7. In the intervention phase obtaining the mean level of 7.63, whereas the baseline phase-2 (A-2) after given intervention to get the mean level of 11. The results above two subjects have meant that there are increased communication skills of children with autism in both subjects.